From consortium design to bioaugmented filters: scalable yeast-based strategies for lead remediation in water systems - Gupta, Nikita; Arunachalam, Sathiavelu (Frontiers in Microbiology, 2025)
Our study aimed to utilize the yeast consortium formed from the native heavy metal-resistant yeasts isolated from the River Cauvery to bioremediate lead. As an extension of the study, the same optimized consortium was further used to augment alginate-based filters to showcase an early proof of concept example that the biosorptive potential of yeast could improve the functionality of these filters. Three yeast strains native to the river Cauvery and highly resistant to heavy metal presence, viz. Clavispora lusitaniae (R4N2), Candida tropicalis (R2N4), and Pichia kudriavzevii (R1N8) were used to design a compatible and synergistic consortium for this study. For optimizing the performance of the consortium over so many independent variables, we took the help of a computational modelling approach, i.e., RSM (Response surface modelling), to narrow down the effective number of experiments. The Box–Behnken design (BBD) matrix within the RSM framework was used extensively in this study. For highlights, in single culture optimization: Candida tropicalis reached near-complete removal at pH 7, biomass 2 g, and Pb2+ 200 mg/L; Clavispora lusitaniae reached maximum removal (~100%) at pH 5.5–7.0, biomass dosage above 1.4 g, and Pb2+ concentrations of 120–200 mg/L; Pichia kudriavzevii performed best at pH 6.13, biomass 1.53 g/L, and Pb2+ concentration of 151.80 mg/L. For the 2-mix consortium (R2N4 + R4N2) removal efficiency over the optimized condition was 93.77% for 100 ppm and 52.42% at 200 ppm. For the 3-mix consortium, removal efficiency was 97.49% at 100 ppm and 52.11% at 200 ppm. The lead removal was further improved when we coupled the consortium with alginate gel slabs. At 100 ppm and 500 ppm, the 2-mix filter assembly removed 99.39 and 93.77% of the Lead, while the 3-mix filter assembly removed 99.97 and 95.19% of the Lead. Lead deposition on the filter surface and cells via biosorption was validated by SEM, FTIR, and EDX experiments. To conclude, our study shows that the bioaugmented filter allows for efficient removal of lead from water at lab-scale operations with further potential for scale-up and industrial usage in wastewater treatment.